WOMEN LEADERSHIP IN ENVIRONMENTAL CONSERVATION IN VIEW OF LAUDATO SI (Journal of Pharmaceutical Negative Results, 2023)
This paper explores the important role of Women leadership in environmental conservation. The Encyclical called “Laudatosi” written by Pope Francis records the importance of women’s leadership as a foundation for preserving nature and its resources. The aim is to explain how women’s leadership fits into taking care of the environmental issues concerning the areas of governance. Women need to be motivated, lifted, and encouraged to safeguard the resources of the earth. Drucker says, “One does not ‘manage’ people. The task is to ‘lead’ people. And the goal is to make productive the specific strengths and knowledge of each individual.” This is what happens when a woman takes lead in the family and society. For she knows well about the strengths and weaknesses of each individual, each one’s capabilities and talents as ahead of the family, community, and society. Thus, as a good leader, the woman has the power to empower, support and sustain everyone to preserve and conserve the environment. She becomes a visible role model to inculcate environmental ethics in the hearts of others.